A classification of web browsing on mobile devices. (February 2015) - Roudaki, A.; Kong, J.; Yu, N.
Abstract: The usage of mobile devices is growing fast. Different approaches have been proposed to improve the user experience of web browsing on mobile devices. This paper comprehensively reviews and compares various techniques for web browsing on mobile devices. We classify approaches of web browsing on mobile devices into three categories: platform-specific mobile design, web page restructuring and zooming based interaction. The platform-specific mobile design technique includes various mobile markup languages and interactive tools that facilitate web designers to manually create a mobile optimized web site. The web page restructuring technique intelligently adapts a desktop web page for web browsing on mobile devices. This technique first discovers closely related information (i.e., page segmentation) and then generates an adaptive layout that fits mobile devices. The zooming based interaction displays a desktop web page within a mobile screen as an overview, which allows a user to zoom in on a specific portion for a detailed reading. Based on the classification, we compare those browsing techniques on mobile devices from six perspectives, i.e., development cost, consistency with the desktop version, dynamic content supports, hardware requirements, display optimization and user operation. We further discuss eight popular commercial mobile browsers. A user study was conducted to evaluate different browsing techniques. This paper demonstrates the state of the art in web browsing on mobile devices, and compares different approaches. Based on the comparison and user study, we propose future developments in web browsing on mobile devices. Highlights: Present a classification of web browsing on mobile devices. Compare different mobile browsing approaches from six perspectives. Conduct a survey research to evaluate different mobile browsing techniques. Propose future developments in mobile browsing.